2020
DOI: 10.22201/ia.01851101p.2020.56.01.10
|View full text |Cite
|
Sign up to set email alerts
|

The Environmental Dependence of the Age of Active Galaxies and the Dependence of the Clustering Properties of Active Galaxies on Age

Abstract: We explore the environmental dependence of the age and the clustering-age dependence of active galaxies in two volume-limited active galaxy samples of the SDSS. In the luminous volume-limited sample, the age of active galaxies apparently depends on environments: at low density the fraction of young galaxies with ages less than 2 Gyr is significantly higher than the one in the high density case, at high density the fraction of old galaxies is significantly higher than the one at low density. Young active galaxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Statistical analyses in these different galaxy samples can reach the same conclusion: galaxies with large stellar velocity dispersions exist preferentially in high density regimes, while galaxies with small stellar velocity dispersions are located preferentially in low density regions. Deng (2014) demonstrated a strong environmental dependence of galaxy age in two volume-limited Main galaxy samples, but Deng & Wen (2020) reported that in the faint volume-limited AGN host galaxy sample, the environmental dependence of the age is fairly weak. Zheng et al (2017) presented the stellar age and metallicity distributions for 1105 galaxies on the SDSS-IV MaNGA (Mapping Nearby Galaxies at APO) (Bundy et al 2015) integral field spectra, and also found that the galaxy age depends on local density.…”
Section: Statistical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical analyses in these different galaxy samples can reach the same conclusion: galaxies with large stellar velocity dispersions exist preferentially in high density regimes, while galaxies with small stellar velocity dispersions are located preferentially in low density regions. Deng (2014) demonstrated a strong environmental dependence of galaxy age in two volume-limited Main galaxy samples, but Deng & Wen (2020) reported that in the faint volume-limited AGN host galaxy sample, the environmental dependence of the age is fairly weak. Zheng et al (2017) presented the stellar age and metallicity distributions for 1105 galaxies on the SDSS-IV MaNGA (Mapping Nearby Galaxies at APO) (Bundy et al 2015) integral field spectra, and also found that the galaxy age depends on local density.…”
Section: Statistical Resultsmentioning
confidence: 99%
“…Zheng et al (2017) presented the stellar age and metallicity distributions for 1105 galaxies on the SDSS-IV MaNGA (Mapping Nearby Galaxies at APO) (Bundy et al 2015) integral field spectra, and also found that the galaxy age depends on local density. Thus, Deng & Wen (2020) believed that the environmental dependence of the age of AGN host galaxies is likely different from the one of genenal galaxies, which merits further studies.…”
Section: Statistical Resultsmentioning
confidence: 99%
“…We used two volume‐limited active galactic nucleus (AGN) host galaxy samples constructed by Deng & Wen (2020), and explored the environmental dependence of the stellar mass in these two volume‐limited AGN host galaxy samples. As shown in Figure 1, in the luminous volume‐limited AGN host sample, the stellar mass of AGN host galaxies apparently depends on local environments: high mass AGN host galaxies exist preferentially in the dense regions of the universe, while low mass AGN host galaxies are located preferentially in low density regions.…”
Section: Discussionmentioning
confidence: 99%
“…Most galaxies of this sample are within redshift region 0.02 ≤ z ≤ 0.2. Deng & Wen (2020) downloaded the data for the Main galaxy sample from the Catalog Archive Server of SDSS Data Release 12 (Alam et al 2015) using the SDSS SQL Search tool (http://www.sdss3.org/dr12/), and extracted 631,968 Main galaxies within the redshift domain of 0.02 ≤ z ≤ 0.2 [the Main galaxies correspond to LEGACY_TARGET1 & (64 | 128 | 256) > 0]. Deng & Wen (2020) selected C, AGN, and Low S/N AGN populations and constructed an apparent magnitude‐limited AGN sample that contains 122,923 AGN host galaxies, then constructed two volume‐limited active galactic nucleus (AGN) host galaxy samples.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation